Financial Performance Evaluation in Property Companies Using the DuPont Method: Insights and Implications - Abdul Manap; Patrice Vincia; Yogi Alfadrus; Nayyara Muthi (IHSA Institute, 2024)
This research examines the financial performance of property companies using the DuPont method, which breaks down Return on Equity (ROE) into three components: profitability, asset turnover, and financial leverage. The study applies this method to a sample of property firms to understand how these factors influence overall financial performance in the real estate sector. Findings indicate that while profitability and asset efficiency are critical for financial success, financial leverage has a significant impact due to the sector's capital-intensive nature. Companies that manage their profit margins, optimize asset use, and maintain balanced leverage typically achieve better financial outcomes. However, the research also highlights limitations of the DuPont method, such as its reliance on historical accounting data and its inability to fully account for market volatility, non-financial factors, and long-term investment dynamics unique to the property sector. To address these limitations, the study suggests integrating the DuPont method with additional analyses that consider market conditions, forward-looking indicators, and non-financial aspects. This comprehensive approach offers a more accurate understanding of financial performance, aiding property managers, investors, and policymakers in making informed decisions.